The Effectiveness of The al-Qur'an Literacy Program In Improving Academic Achievement - Saif Aziz, Muhammad; Arsyad, Junaidi (At-Tarbiyat, 2024)
The evaluation of the Al-Qur'an literacy program carried out at the Darul Ulum Budi Agung Medan Private MTs, aims to assess the impact of the program on students' Al-Qur'an Hadith learning achievement. Researchers apply qualitative descriptive methods with formative and summative evaluation models. Data collection techniques include observation, interviews, and documentation studies, which are then analyzed through data reduction, data presentation, and drawing conclusions. The research results showed that the Al-Qur'an literacy program had a positive impact on students' Al-Qur'an Hadith learning achievement. Students experienced improvements in reading, memorizing and understanding verses of the Qur'an and showed increased engagement in learning. Apart from that, this program also contributes to increasing the number of tahfiz graduates every year in madrasas. These findings indicate that the Al-Qur'an literacy program and its implementation can be a valuable reference for other schools in efforts to improve student learning achievement.